Prematurity and congenital malformations differ according to the type of pregestational diabetes - Monica Ballesteros; A Guarque; M Ingles; N Vilanova; M Lopez; L Martin; M Jane; L Puerto; M Martinez; M De la Flor; J Vendrell; A Megia (BMC Pregnancy and Childbirth, 2024)
Abstract Background Diabetes mellitus (DM) is the most common metabolic disorder in pregnancy. Women with Type 2 DM seems to have no better perinatal outcomes than those with Type 1 DM. Methods Single-center prospective cohort observational study. Pregnant women with diabetes (141 with Type 1 DM and 124 with Type 2 DM) that were followed in the university hospital between 2009 and 2021 were included in this study. Clinical data and obstetric and perinatal outcomes were collected. Results As expected, women with Type 1 DM were younger and had a longer duration of diabetes than women with Type 2 DM. Obesity and chronic hypertension were higher in the group of women with Type 2 DM and their value of HbA1c in the second and third trimesters were lower than in Type 1 DM. No differences in prematurity were found, but more extreme prematurity was observed in Type 2 DM, as well as a higher rate of congenital malformations. The frequency of hypoglycemia and the weight of the newborn was higher in Type 1 DM. The maternal independent factors related to the weight of the newborn were: the glycemic control at the third trimester, the weight gain during pregnancy, and pregestational BMI. Conclusions Newborns born to mothers with Type 1 DM were larger and had a higher frequency of hypoglycemia, while congenital malformations and precocious preterm was more associated to Type 2 DM. Metabolic control, weight gain and pregestational weight were important determinants of both obstetric and neonatal complications.